Retraction Note: Progranulin causes adipose insulin resistance via increased autophagy resulting from activated oxidative stress and endoplasmic reticulum stress - Qinyue Guo; Lin Xu; Huixia Li; Hongzhi Sun; Jiali Liu; Shufang Wu; Bo Zhou (Lipids in Health and Disease, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12944-017-0425-6.